Dataset of some added-lignin thermoformed pulpsZenodo - Jost Ruwoldt (Data in Brief)
This data article summarizes the material properties of some added-lignin thermoformed pulps (ALTPs). This type of molded pulp is particularly suited for replacing plastics in environments, where moisture is encountered, as the lignin reduces the transport and adsorption of water. The dataset was measured on wet formed substrates with either softwood chemi-thermomechanical pulp (CTMP) or northern bleached softwood Kraft pulp (NBSK). To the basis weight of 500 g/m2 pulp fibers (6 g pulp per 15 cm by 8 cm substrate area) were added 0.8 g of lignin, constituting a loading of 13.33 % added lignin per dry fibers. Right after forming, the sheets were pressed at 20 bar and room temperature between blotting paper to remove excess water, air dried overnight, and subsequently thermopressed at 175 °C and 200 bar. The resulting materials were measured and weighed, cut into test stripes with 15 mm width, and tensile tested. The absorption of water (water uptake) was measured after immersing the test pieces (15 mm by 15 mm) in distilled water for 24 h. The data shows slight increases in density after lignin addition and, on average, a reduction in water absorption. In particular, adding acetylated lignin significantly lowered the water uptake, as compared to the regular soda or Kraft lignin. The tensile strength and stiffness of CTMP was the same or lower after lignin addition, whereas NBSK showed increases in both stiffness and strength.